FLUORESCENCE DIAGNOSIS AND PHOTODYNAMIC THERAPY IN COMBINED TREATMENT OF CHOLANGIOCARCINOMA - A. A. Shiryaev; G. Kh. Musaev; M. V. Loshenov; A. V. Borodkin; V. V. Levkin; N. L. Okhotnikova; V. V. Volkov; V. I. Makarov; V. B. Loshenov (Biomedical Photonics)
The results of the pilot study of combined treatment for non-resectable cholangiocarcinoma complicated with obstructive jaundice are represented this paper. Method included percutaneous transhepatic biliary drainage, endoscopic fluorescence diagnosis, photodynamic therapy of tumor stricture, and stenting of bile ducts. Fourteen patients who underwent the treatment in the surgery department clinic of I.M. Sechenov First Moscow State Medical University were enrolled in the study. Fluorescence diagnosis and photodynamic therapy were carried out using photosensitizers photosens (0.5 mg/kg), fotolon (1 mg/kg), and radachlorin (1 mg/kg). The average light dose for one session was 115±5 J/cm2. Fluorescence diagnosis using endoscopic video-fluorescence system for endoscopy and minimally invasive surgery allowed to obtain videoassisted fluorescence image of the tumor and to measure level of photosensitizer fluorescence in tumor in all patients. Malignant tumor was confirmed by morphological study in 12 patients, biopsy of material for morphological study failed in 2 patients with Klatskin tumor. The preliminary results of combined minimally invasive treatment were assessed as promising. The survival time in 4 patients after treatment accounted for 21, 17, 13 and 11 months, respectively. For now 5 patients are under follow-up. Follow-up periods are 13 and 19 months in 2 of them and from 4 to 6 months in 3 of them. Five patients with multiple distant metastases before the treatment died in 3±1 months after therapy. The average lifetime in the treatment group is 9.5 months up to date, however the duration is expected to belonger because 5 of 14 patients are alive.